2007
DOI: 10.1185/030079907x253636
|View full text |Cite
|
Sign up to set email alerts
|

Transferring type 2 diabetes patients with uncontrolled glycaemia from biphasic human insulin to biphasic insulin aspart 30: experiences from the PRESENT study

Abstract: In this observational study, in the type 2 diabetes mellitus patients who were poorly controlled on BHI, glycaemia improved when transferred to BIAsp30, and a lower incidence or rate of hypoglycaemia was observed in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
21
3
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 18 publications
8
21
3
1
Order By: Relevance
“…On the other hand, Boehm et al (7) and the PRESENT study (9) reported no significant difference in weight gain between BHI30-and BIAsp30-treated patients, a finding which is inconsistent with our study results.…”
Section: Discussioncontrasting
confidence: 57%
“…On the other hand, Boehm et al (7) and the PRESENT study (9) reported no significant difference in weight gain between BHI30-and BIAsp30-treated patients, a finding which is inconsistent with our study results.…”
Section: Discussioncontrasting
confidence: 57%
“…Observational studies are suitable for this 17 and can provide information on insulin dosing and titration patterns in the real-life clinical setting among a broad range of patients with diabetes-related comorbidities and complications. Previous observational studies have reported improved glycemic control and a reduced incidence of hypoglycemia in patients switching from BHI to BIAsp 30 18,19 . However, mid-and high-mix formulations (BIAsp 50 and 70) are also available: individual needs vary in diabetes and certain groups of patients require different prandial insulin coverage due to prandial intake.…”
Section: Introductionmentioning
confidence: 95%
“…26 The Physicians' Routine Evaluation of Safety and Efficacy of NovoMix 30 Therapy (PRESENT) study was an open-label, multicountry, single-arm, observational study that enrolled over 20,000 patients with type 2 diabetes, both insulin-naïve and insulintreated, with and without concurrent OAD usage, and has been reported extensively elsewhere. [27][28][29][30] Patients in PRESENT were treated with BIAsp30 twice-daily at dosages that varied according to the discretion of their physician and were not treated to any specific glycaemic control targets. Data from the subset of patients transferred to BIAsp30 from biphasic human insulin (BHI) in China are analysed here (n=2289), where significant improvements in glycosy-y y lated haemoglobin (HbA 1c ) levels (-1.82%; P<0.001) and substantial reductions in hy-y y poglycaemic events (-1100 events [major and minor] per 100 patient years; P<0.001) were observed in poorly controlled patients (baseline HbA 1c = 8.81%) over 3 months.…”
Section: Introductionmentioning
confidence: 99%